Application of diagnostic tools for optimised treatment and management of coccidiosis in kiwi (Apteryx spp.) : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy (PhD) in Veterinary Sciences at Massey University, Manawatū, New Zealand. EMBARGOED to 24 January 2027. - Scheltema, Emma Margaret (Massey University, 2024)
Coccidiosis, a disease caused by infection with the protozoan parasite, Eimeria spp., is currently the main limiting disease in captive and creche-reared kiwi and can cause significant morbidity and mortality in young birds. There are at least five species of Eimeria that infect kiwi, and they are usually present as a mixed species infection. These parasites cause damage to tissues of the intestine and occasionally to other organs including the liver, kidneys, lungs, and spleen. Infection is managed in captivity through husbandry and medication, primarily via therapeutic treatment with the anticoccidial, toltrazuril (Baycox®, Bayer, Leverkusen, Germany). However, there is some evidence that this drug is not always effective, and there has been no research to date into safe and effective alternatives. Thus, effective management of this disease in infected birds is limited by a lack of evidence-based therapeutic options. The overall objective of this study was to improve the detection and diagnosis of kiwi Eimeria spp. through the development of a molecular tool, that could then be applied to assist in identifying safe and effective prophylactic and/or therapeutic treatments for the control of coccidiosis in kiwi chicks. To achieve this, we developed a molecular diagnostic tool (qPCR) to measure the diversity of Eimeria species present in mixed infections in kiwi. This tool was applied to preserved tissue samples to identify the tissue specificity (in intestine, liver, kidney, lungs, and spleen) of different kiwi Eimeria species, which may have consequences for the success of drug treatment. Following the development of normal blood biochemical and haematological reference intervals in healthy kiwi chicks as a baseline, a safety and pharmacokinetic study of five anticoccidial drugs (amprolium 15mg/kg, decoquinate 0.5mg/kg, diclazuril 5mg/kg, trimethoprim-sulphamethoxazole 20:100mg/kg and toltrazuril 25 mg/kg) given as single doses to healthy kiwi chicks was carried out. We then trialled one of these drugs, diclazuril, given both prophylactically in-feed (0.5mg/kg q24h) and as a therapeutic treatment (5mg/kg single dose) in naturally infected kiwi in a field study at a captive-rearing centre. In combination with standard faecal oocyst counts, the molecular tool was used to assist in Eimeria species identification from faecal samples from treated and untreated birds. We were able to establish the presence of a single Eimeria species infecting extra-intestinal tissues, described here as Eimeria koka, and isolated another species Eimeria kiwii from the intestine. Baseline biochemical and haematological parameters and the safety and pharmacokinetics of four anticoccidial drugs were established in healthy three-to-four-week-old kiwi chicks. We were unable to determine the pharmacokinetics of one of the drugs, decoquinate. The use of diclazuril in-feed was well-tolerated by kiwi chicks and while there was no observed difference in body weight or feed intake between treated and untreated control chicks, diclazuril-treated birds shed significantly fewer oocysts than control chicks. A small number of birds were dosed therapeutically with diclazuril, and we observed a decrease in oocyst shedding equivalent to the toltrazuril-treated control group (standard management), however, more data is required to confirm this pattern. Not all kiwi Eimeria species were found to be equally susceptible to treatment with diclazuril, with changes in species composition observed in treated kiwi. The molecular assay developed in this study has a range of applications to address questions about kiwi Eimeria biology and control. We hypothesise that the newly described Eimeria koka is likely the only Eimeria species infecting kiwi that migrates extra-intestinally, to infect the kidneys, and under severe infections, probably disseminates to other organs. Further testing of the response of this species to drug treatment is required; it is likely more challenging to treat due to its location in the body. All drugs trialled in kiwi appear to be relatively safe at the given doses. Diclazuril appears to be partially effective in the prevention and therapeutic treatment of coccidiosis in kiwi. Further investigation into dose rate and period, and the addition of other safe and effective drugs to build a sustainable, rotational drug dosing scheme is highly recommended before the integration of any new treatments into captive management protocol. This study is the first to establish the safety and pharmacokinetics of anticoccidial drugs in kiwi, and to demonstrate the efficacy of diclazuril to treat coccidia infection in kiwi. The methods developed herein lay the foundation for establishing the safety and efficacy of other drugs for treating this disease and will ideally contribute towards the development of more sustainable coccidiosis management plans for kiwi. The identification of optimum treatments for coccidiosis in kiwi is of high importance for the ongoing maintenance of captive-reared kiwi health and welfare, and the success of this form of ex-situ conservation intervention.
Keywords: Veterinary Science; Parasitology; Wildlife Health; Conservation